Teachers' Strategies in Enhancing Professionalism in the Era of Society 5.0 - Eko Firman Susilo; Yuannisah Aini Nasution; Rindiyani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The rapid acceleration of digital technology has introduced the paradigm of Society 5.0, a human-centered society that leverages cutting-edge artificial intelligence, big data, and the Internet of Things to solve complex social challenges. In the educational sphere, this paradigm shift requires a radical transformation of teacher professionalism, transitioning instructors from traditional transmitters of knowledge into dynamic facilitators, digital innovators, and empathetic mentors. This study investigates the comprehensive strategies implemented by teachers at SMK Harapan Al Washliyah Titi Aloban to enhance their professional capabilities in response to the demands of Society 5.0. Utilizing a quantitative descriptive survey design, data were collected on June 11, 2026, from 12 active teachers using a structured 13-item questionnaire spanning four key dimensions: digital adaptation and literacy, pedagogical and professional competence enhancement, professional collaboration and networking, and humanistic character reinforcement. The overall empirical findings demonstrate that teacher professionalism strategies achieved a high average implementation rate of 77.86%, categorized as 'Good'. Specifically, humanistic character reinforcement recorded the highest performance score at 84.72% ('Very Good'), highlighting teachers' deep commitment to emotional support, ethical digital guidance, and student creativity. Pedagogical and professional enhancement scored 76.04% ('Good'), collaboration and networking reached 75.69% ('Good'), and digital adaptation scored 75.00% ('Good'). Although digital literacy was strong regarding independent educational technology tracking (85.42%) and artificial intelligence integration (77.08%), the formal adoption of Learning Management Systems (LMS) registered the lowest score at 62.50%. The contribution of these findings lies in providing an empirical framework that highlights the necessity of combining human-centered pedagogy with targeted institutional infrastructure support to bridge the digital implementation gap in vocational education.